(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
Plasma shielding effects on the energy levels and radiative properties of He-like Ca\(^18+\) ion under dense plasma conditions have been studied. For this purpose, the multiconfiguration Dirac-Fock method has been implemented by incorporating the ion sphere model potential as a modified interaction potential between the electron and the nucleus. To check the authenticity of our results, independent calculations have been performed using the modified relativistic configuration interaction method. It is observed that the transition energies associated with \(Δ n = 0\) transitions are blue shifted, whereas red shifted for \(Δ n eq 0\) transitions. The variation in transition probabilities and weighted oscillator strengths with plasma densities has also been analyzed. The present results should be beneficial in the plasma modeling and fusion plasma research applications.